Behavior-specific praise: Enhancing on-task behavior in a rural elementary school - Newton, Nicholas A.; Royer, David James; Hogg, Jennifer A.; Priddy, Amber (Frontiers in Education, 2024)
Behavior-specific praise (BSP) is a low-intensity strategy used to reinforce positive student behaviors in school settings. BSP is currently a potentially evidence-based practice, with more studies with three or more participants needed to contribute to the literature base. This study investigated the impact of teacher-delivered BSP on student on-task behavior in an inclusive second grade classroom taught by a general and special education coteacher dyad in a rural Southeast school. Using an A-B-A-B withdrawal design, we observed the on-task behavior of four students with emotional and/or behavioral disorders (EBD) when the coteaching pair increased their rates of BSP after a brief training. All four students increased on-task behavior during BSP intervention conditions. Social validity questionnaires identified a positive impression from three out of four students and both teachers about the implementation of BSP in the classroom. Limitations and future directions are discussed.